2018
DOI: 10.1080/02786826.2018.1433293
|View full text |Cite
|
Sign up to set email alerts
|

Fate of pyrazines in the flavored liquids of e-cigarettes

Abstract: Popularity of electronic cigarettes (ECIGs) has increased tremendously among young people, in part due to flavoring additives in ECIG liquids. Pyrazines are an important class of these additives, and their presence in tobacco cigarettes has been correlated with increased acceptability of smoking among smokers and bystanders. Pyrazine use by the tobacco industry is therefore thought to encourage smoking. However, the extent of transfer of pyrazines present in the liquid to aerosols upon vaping remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The introduced method separates phenolic compounds from the matrix due to the selective solubility of the analytes. A similar approach was previously reported by our group for analyzing nicotine and pyrazine in ECIG liquids and aerosols. , …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The introduced method separates phenolic compounds from the matrix due to the selective solubility of the analytes. A similar approach was previously reported by our group for analyzing nicotine and pyrazine in ECIG liquids and aerosols. , …”
Section: Discussionmentioning
confidence: 79%
“…A similar approach was previously reported by our group for analyzing nicotine and pyrazine in ECIG liquids and aerosols. 36,37 The literature has shown that the oxidation and thermal degradation of the main liquid components (PG and VG) led to the formation of carbonyl compounds, radicals, ROS, and other compounds. 38−40 Per contra, the formation of other families of toxicants, like aryl compounds, could be attributed to the addition reactions of radicals or unsaturated hydrocarbon intermediates.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Uchiyama et al [106] observed large variations in carbonyl concentrations between and within unnamed devices. El-Hage et al [107] reported the transfer of pyrazines, a class of flavoring compounds, from eliquid to aerosol. Rawlinson et al [108] identified the chemical profiles of aerosols generated from 4 e-liquids contained between 30-90 compounds mostly characterized as "unknown" exceeding the 5 ng/puff threshold which may include PAHs.…”
Section: Additional Articlesmentioning
confidence: 99%
“…Among the many AlkPyrs, ethyl-dimethylpyrazines (EDMPs) are the most potent odorants (perceived as roasty and sweet) and generate a broad market demand. The 235- and 325-EDMP isomers ( 7 and 8 ) (Figure ) contribute to the desirable taste of tea and are also used as flavoring agents, food additives, fragrances, and added ingredients in cigarettes; related AlkPyrs are found in e-cigarettes . Also, the commercially available mixtures of 7 and 8 were chromatographically separated to show that each distinctly affected the behavioral response of fire ants in an electroantennogram study .…”
Section: Introductionmentioning
confidence: 99%
“…The 235and 325-EDMP isomers (7 and 8) (Figure 1) contribute to the desirable taste of tea 27−29 and are also used as flavoring agents, food additives, fragrances, 30 and added ingredients in cigarettes; 31 related AlkPyrs are found in e-cigarettes. 32 Also, the commercially available mixtures of 7 and 8 were chromatographically separated to show that each distinctly affected the behavioral response of fire ants in an electroantennogram study. 33 Given the broad chemosensory application of EDMPs, several accounts highlight industrial syntheses and separation of these commodity compounds to address production bottlenecks.…”
Section: ■ Introductionmentioning
confidence: 99%